P2X7 receptor blockade prevents ATP excitotoxicity in neurons and reduces brain damage after ischemia - Joana Arbeloa (Neurobiology of Disease, 2012)
Overactivation of subtype P2X7 receptors can induce excitotoxic neuronal death by calcium (Ca2+) overload. In this study, we characterize the functional properties of P2X7 receptors using electrophysiology and Ca2+ monitoring in primary cortical neuron cultures and in brain slices. Both electrical responses and Ca2+ influx induced by ATP and benzoyl-ATP were reduced by Brilliant Blue G (BBG) at concentrations which specifically inhibit P2X7 receptors. In turn, oxygen-glucose deprivation (OGD) caused neuronal death that was reduced with BBG application. OGD in neuron cultures and brain slices generated an inward current, which was delayed and reduced by BBG. To assess the relevance of these in vitro findings, we used middle cerebral artery occlusion in rats as a model of transient focal cerebral ischemia to study the neuroprotective effect of BBG in vivo. Treatment with BBG (twice per day, 30 mg/kg) produced a 60% reduction in the extent of brain damage compared to treatment with vehicle alone. These results show that P2X7 purinergic receptors mediate tissue damage after OGD in neurons and following transient brain ischemia. Therefore, these receptors are a relevant molecular target for the development of new treatments to attenuate brain damage following stroke.